An Evaluation of 3-Rhamnosylquercetin, a Glycosylated Form of Quercetin, against the Myotoxic and Edematogenic Effects of sPLA2 from Crotalus durissus terrificus. (18th February 2014) - Toyama, Daniela de Oliveira; Gaeta, Henrique Hessel; Pinho, Marcus Vinícius Terashima de; Ferreira, Marcelo José Pena; Romoff, Paulete; Matioli, Fábio Filippi; Magro, Angelo José; Fontes, Marcos Roberto de Mattos; Toyama, Marcos Hikari
Abstract : This paper shows the results of quercitrin effects on the structure and biological activity of secretory phospholipase (sPLA2 ) from Crotalus durissus terrificus, which is the main toxin involved in the pharmacological effects of this snake venom. According to our mass spectrometry and circular dichroism results, quercetin was able to promote a chemical modification of some amino acid residues and modify the secondary structure of C. d. terrificus sPLA2 . Moreover, molecular docking studies showed that quercitrin can establish chemical interactions with some of the crucial amino acid residues involved in the enzymatic activity of the sPLA2, indicating that this flavonoid could also physically impair substrate molecule access to the catalytic site of the toxin. Additionally, in vitro and in vivo assays showed that the quercitrin strongly diminished the catalytic activity of the protein, altered its Vmax and Km values, and presented a more potent inhibition of essential pharmacological activities in the C. d. terrificus sPLA2, such as its myotoxicity and edematogenic effect, in comparison to quercetin. Thus, we concluded that the rhamnose group found in quercitrin is most likely essential to the antivenom activities of this flavonoid against C. d. terrificus sPLA2 .